1983
DOI: 10.1021/jo00153a009
|View full text |Cite
|
Sign up to set email alerts
|

Piperazino-functionalized silica gel as a deblocking-scavenging agent for the 9-fluorenylmethyloxycarbonyl amino-protecting group

Abstract: Bonding cyclic secondary amino residues to the surface of silica gel has given insoluble reagents capable of deblocking the 9-fluorenylmethyloxycarbonyl amino-protecting group and at the same time scavenging the dibenzofulvene (DBF) liberated in the deblocking process. A piperazino silica reagent 6 bearing approximately 1.1 mequiv of NH/g was easiest to prepare by reaction of trimethoxysilane 5 with chromatographic-grade silica.After use, spent reagent could be regenerated by treatment with excess piperidine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…The attempts aimed at the isolation of these new compounds failed because 1 was regenerated instead. Therefore, we investigated the formation of these compounds by 1 H NMR spectroscopy (see the Experimental section), and we noted the presence of an equilibrium between 1 , NMP, and the apparently unstable Michael‐type adducts 5 and 6 (Scheme ) analogous to that described for dibenzofulvene 9, 10. However, under the aforementioned experimental conditions, the amount of 1 was substantial, and the depression of the polymerization can be considered an interesting proof of the proposed mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…The attempts aimed at the isolation of these new compounds failed because 1 was regenerated instead. Therefore, we investigated the formation of these compounds by 1 H NMR spectroscopy (see the Experimental section), and we noted the presence of an equilibrium between 1 , NMP, and the apparently unstable Michael‐type adducts 5 and 6 (Scheme ) analogous to that described for dibenzofulvene 9, 10. However, under the aforementioned experimental conditions, the amount of 1 was substantial, and the depression of the polymerization can be considered an interesting proof of the proposed mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…piperazine, piperidine) in organic solvents. 53,54 Applied for the first time for SPPS by two different laboratories independently. 55,56 Since then, several optimized removal conditions for SPS have been described, the most relevant being: 20% piperidine in DMF, 55 which is the most common, 1-5% DBU in DMF, 57,58 morpholine-DMF (1:1) 59 or 2% HOBt, 2% hexamethyleneimine, 25% N-methylpyrrolidine in DMSO-NMP (1:1), 60 Fmoc α-amino protection has been used for the SPS of several relevant peptides using the so-called Fmoc/ t Bu strategy, the production in Tm scale of the T20 peptide being one of the most important examples.…”
Section: Protecting Groups Removed By Basementioning
confidence: 99%
“…Bae et al reported [6] that the reaction needs to be refluxed in toluene for 12 h. The silica can also be functionalized by refluxing in toluene for 24 h. This was followed by soxhlet extraction [9,10] with different organic solvents. Several other researchers had reported the functionalization of silica (which was pre-dried at 100 • C at 2 mm Hg for 6 h) by refluxing it with CPTES in toluene [11] for 18 h. Paul et al [3] showed that 3-(chloropropyl)trimethoxysilane * Corresponding author. Fax: +60 4 6574854.…”
Section: Introductionmentioning
confidence: 99%